Sistem Pendukung Keputusan Sistem Pendukung Keputusan Penentuan Dosen Terbaik Di Universitas Wiraraja Menggunakan Metode AHP - rieza, wariezatul hasanah; Iddrus, Iddrus (Journal of Advanced Research in Informatics, 2025)
The selection of the best lecturer at Wiraraja University has been conducted manually, potentially causing inefficiency, subjectivity, and difficulties in managing complex data. This research aims to develop a web-based Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method to enhance objectivity, transparency, and assessment accuracy. The system employs four evaluation criteria: (1) Education & Teaching, (2) Research, (3) Community Service, and (4) Supporting Activities. The AHP method calculates criteria and alternative priority weights through pairwise comparisons, followed by a consistency ratio (CR) calculation to ensure judgment consistency. System implementation using PHP, HTML, and MySQL demonstrates improved selection efficiency, reduced recording errors, and data-based ranking of the best lecturers. User testing evaluation confirms optimal system functionality with a consistency rate (CR < 0.1). This system is expected to support strategic university decision- making more fairly and measurably.